Renal resistive index in healthy children - Murat, A; Akarsu, S; Ozdemir, H; Yildirim, H; Kalender, O (Elsevier Ireland Ltd, 2005)
Objective: The objective of the study was to investigate the relationship between age and renal resistive index (RI) and to determine the normal values and ranges of RI in intrarenal arteries in healthy children. Materials and method: Color duplex Doppler sonography of interlobar or arcuate arteries was performed in I 15 children without clinical or laboratory pathologic changes of the urinary tract. Of these 115 healthy children. 23 were under 12 months of age (group 1), 24 between 12 and 35 months (group 2), 23 between 36 and 71 months (group 3), and 45 between 72 months and 16 years (group-4). Normative data for RI were established for each age group. Results: When age groups were compared. statistically significant differences were observed between age groups 1 and 2 (P = 0.001). 1 and 31 (P = 0.00) I and 4 (P = 0.00) and 2 and 4 (P = 0.00). No significant differences were observed between age groups 2 and 3 (P = 0.452). and 3 and 4 (P = 0.078). There was no significant difference between mean RI values of fight and left kidney within any age group (P = 0.315). Conclusion: Results obtained in this study demonstrates that RI is age dependent; it is the highest at birth. from birth declines gradually with increasing a e and stabilizes in a certain range (mean RI range regarded as normal for adults) by reaching adult levels. (C) 2004 Elsevier Ireland Ltd. All rights reserved.
Keywords: Doppler ultrasound; resistive index; healthy children